2015
DOI: 10.1007/s11746-015-2699-z
|View full text |Cite
|
Sign up to set email alerts
|

4‐Hydroxynonenal (HNE), a Toxic Aldehyde in French Fries from Fast Food Restaurants

Abstract: The toxic lipid peroxidation product, α,β,4‐hydroxy‐2‐trans‐nonenal (HNE) concentration, was measured in French fries (FF) from six local fast food restaurants. FF were purchased between 2 and 3 pm from all six restaurants. FF were also purchased at 12, 2, 4, 6 pm from one and at 1, 3, 5, 7 pm from another restaurant. Samples were analyzed for total fat, fatty acid distribution and for HNE by high performance liquid chromatography (HPLC). HNE was confirmed by HPLC/MS. HNE concentrations in FF from the 6 fast f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Seppanen & Csallany () found that the level of HNE in the potatoes fried in soya bean oil was 59.64 ± 11.91 mg per 100 g. This was considerably higher than what we found in our FF, and this could be because of the air bubbles in the oil. Nonetheless, our results corroborate the findings of Csallany et al (), in which the level of HNE in the commercial FF fried in linoleic acid‐rich oils was approximately 7.47–32.15 μg.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Seppanen & Csallany () found that the level of HNE in the potatoes fried in soya bean oil was 59.64 ± 11.91 mg per 100 g. This was considerably higher than what we found in our FF, and this could be because of the air bubbles in the oil. Nonetheless, our results corroborate the findings of Csallany et al (), in which the level of HNE in the commercial FF fried in linoleic acid‐rich oils was approximately 7.47–32.15 μg.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, they contribute to the pathogenesis of many diseases and are considered mutagenic, carcinogenic and cytotoxic (Esterbauer et al, 1991;Sousa et al, 2017;Wang et al, 2017;Soulage et al, 2018). Particularly, MDA and HNE are considered by the Belgian Superior Health Council to be of major concern to human health (Douny et al, 2015), and so is HNE in the United States (Csallany et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…[7] The ingestion of MDA, HHE, and HNE has been considered to promote inflammation, disturb the redox homeostasis, and cause several diseases including atherogenesis, diabetes, and even cancer. [8,9] MDA, HHE, and HNE have attracted attention in some regions: the Belgian Superior Health Council has considered MDA and HNE as major concerns for human health; [10] HNE has been recognized as a potential public health concern in America; [11] and the European Food Safety Authority scientific committee has suggested the threshold of toxicological concern (TTC) level of exposure for MDA, HHE, and HNE as 30, 1.5, and 1.5 μg kg À1 bw/day, respectively. [4] Remarkably, the number of scientific articles reporting MDA, HHE, and HNE as related to the food domain are very few (Table S1, Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…It was not until HHE and HNE were detected in infant formulas that they attracted the interest of the food science community (Surh et al, 2007;Michalski et al, 2008). HNE has recently been recognised as a potential major human health concern by the Belgian Superior Health Council and public health officials in the United States (Csallany et al, 2015;Douny et al, 2015). The scientific committee of the European Food Safety Authority (EFSA) has established a threshold of toxicological concern (TTC) of 1.5 lg per kg body weight (bw) per day for both HHE and HNE (Papastergiadis et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…HHE and HNE were detected in 16% and 63% of the samples, respectively, and were especially concentrated in foods rich in PUFA that were processed at high temperatures. Other studies determined that HHE and HNE could be incorporated into fried foods during the frying process (Csallany et al, 2015;Ma & Liu, 2017). HHE and HNE formation during digestion of fish oil and cod liver oil had also been examined, and results indicated HHE and HNE could enter the bloodstream once they reached the small intestine (Larsson et al, 2016;Steppeler et al, 2016).…”
Section: Introductionmentioning
confidence: 99%